2013
DOI: 10.1016/j.molonc.2013.11.007
|View full text |Cite
|
Sign up to set email alerts
|

TORC1 and class I HDAC inhibitors synergize to suppress mature B cell neoplasms

Abstract: Enhanced proliferative signaling and loss of cell cycle regulation are essential for cancer progression. Increased mitogenic signaling through activation of the mTOR pathway, coupled with deregulation of the Cyclin D/retinoblastoma (Rb) pathway is a common feature of lymphoid malignancies, including plasmacytoma (PCT), multiple myeloma (MM), Burkitt’s lymphoma (BL), and mantle cell lymphoma (MCL). Here we evaluate the synergy of pharmacologically affecting both of these critical pathways using the mTOR inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 70 publications
1
38
0
Order By: Relevance
“…Our in vivo data using the MDA-MB-231 cell line are consistent with these data in that we saw minimal effect when entinostat was administered alone, but in combination with rapamycin we saw a significant reduction in tumor growth. The synergistic effect of combining rapamycin with HDAC inhibition has been reported in several tumor models [2831] and we have now extended this to breast cancer cells. HDAC inhibition as an approach for the treatment of breast cancer has been pursued as both a single agent and in combination with other drugs [47] and entinostat is currently the subject of a number of clinical trials in breast cancer (in combination with exemestane, Clinical Trials Identifier: NCT02115282; in combination with Fulvestrant: NCT02115594, and in combination with lapatinib, or lapatinib and trastuzumab: NCT01434303).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Our in vivo data using the MDA-MB-231 cell line are consistent with these data in that we saw minimal effect when entinostat was administered alone, but in combination with rapamycin we saw a significant reduction in tumor growth. The synergistic effect of combining rapamycin with HDAC inhibition has been reported in several tumor models [2831] and we have now extended this to breast cancer cells. HDAC inhibition as an approach for the treatment of breast cancer has been pursued as both a single agent and in combination with other drugs [47] and entinostat is currently the subject of a number of clinical trials in breast cancer (in combination with exemestane, Clinical Trials Identifier: NCT02115282; in combination with Fulvestrant: NCT02115594, and in combination with lapatinib, or lapatinib and trastuzumab: NCT01434303).…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have shown that the HDACi LBH589 degrades aurora A and B kinases in renal cancer cells [26] and TSA reduces the levels of PLK1 protein in HeLa cells [27]. The combination of rapamycin and HDAC inhibition has been studied in models of number of cancers [2831] and currently the combination of temsirolimus and vorinostat is undergoing phase 1 trial in patients with metastatic prostate cancer (ClinicalTrials.gov Identifier: NCT01174199), however, the combination of mTOR inhibition and HDAC inhibition has not been extensively studied in models of breast cancer. TSA has not been developed for therapeutic use, so we assessed two HDAC inhibitors under clinical development, suberoylanilide hydroxamic acid (SAHA) and entinostat (MS-275), in combination with rapamycin.…”
Section: Resultsmentioning
confidence: 99%
“…45 Another rationale is to explore synergistic activity in vitro, similar to that of the combination of rapalogues and histone deacetylase inhibitors such as panobinostat. 46 However, in a phase I trial combining everolimus with panobinostat in lymphoma patients, severe thrombocytopenia occurred. 47 Recently, based on in vitro synergism, 48 the combination of everolimus and lenalidomide was explored in a phase I trial and was found to have promising activity and acceptable tolerability in patients with relapsed MM.…”
mentioning
confidence: 99%
“…Although the underlying mechanisms are not clear, HDAC inhibitors are wildly used in combination with chemotherapeutic agents to enhance anticancer activity [4649]. As a selective class I HDAC inhibitor, entinostat has shown promising efficacy in the treatment of B cell lymphomas [39,40,50]. Our previous studies also revealed that entinostat in combination with melphalan or bendamustine synergistically induced growth inhibition and apoptosis in MM cells [51,52].…”
Section: Discussionmentioning
confidence: 99%